Examining the effect of absorptive capacity on waste processing method adoption: A case study on Chinese pig farms. (1st April 2019) - Yan, Zhenyu; Wang, Chao; Xu, Jiapeng; Huo, Xuexi; Hussain, Qaiser
Abstract: The ability of farms to assimilate and exploit new knowledge is imperative. Previous research on the adoption of animal waste processing technologies has only focused on the farm level, and no attention has been paid to the role of organizational resources in this decision. This study examines the effect of organizational resources like absorptive capacity on Chinese pig farms' waste processing method adoption. We also account for farm-level characteristics such as respondents' individual characteristics, production and business operation characteristics, and policy environment, to help better discuss the factors influencing adoption of waste processing methods. Using a survey of 243 scale pig farms, we find that the ability to acquire, assimilate, transform and exploit knowledge about products and processes has a significant impact on the rate at which waste processing methods with higher COD (TN) removal rate get adopted. Other positive determinants include the proportion of income from livestock breeding, annual inventory, general employee training, and household education level. Highlights: Absorptive capacity refers to an entity's capacity to identify, evaluate, assimilate, and exploit new external technologies. The absorptive capacity of pig farms has a significant impact on their adoption of waste processing methods with higher COD(TN) removal rates. The "aerobic + anaerobic" waste processing method was the one with the highest COD (TN) removal rate in the sample area.